Polybaric heterogeneous mush zones: From deep to shallow beneath the ultraslow-spreading Southwest Indian Ridge - Cui, Xiang; Zhou, Huaiyang; Koepke, J.; Ma, Qiang (Earth and planetary science letters, 2025)
•Our samples contain a unique subophitic mineral assemblage unlike typical PUB.•We propose multiple mush zones at different depths beneath the SWIR.•These mush zones have varied compositions and distinct magmatic processes.•Phenocrysts show strong compositional heterogeneity, which diminishes in the matrix. The formation and evolution of the oceanic lithosphere are controlled by complex magmatic processes that remain subjects of ongoing research. Studies on Plagioclase Ultraphyric Basalt (PUB) have greatly expanded our understanding of these processes over the past two decades. In this study, we report a novel type of PUB sampled from the ultraslow-spreading Southwest Indian Ridge (SWIR), revealing two distinct mineral assemblages that coexist within individual samples. Group 1 minerals, dominated by high-anorthite (An) plagioclase macrocrysts with core An values up to 86 and high-Mg olivine with core Fo (molar Mg/(Mg+Fe) × 100) values up to 88, are characterized by cotectic crystallization. They represent deep, anorthositic mush zones that have undergone multiple magma replenishments. In contrast, Group 2 minerals, consisting of clinopyroxene oikocrysts and plagioclase chadacrysts, display features of fractional crystallization from shallower gabbroic mush zones. The broad range of 87Sr/86Sr ratios in Group 1 plagioclase macrocrysts (0.70280–0.70375) and Group 2 plagioclase chadacrysts (0.70285–0.70388), coupled with a narrower isotopic range in matrix plagioclase laths (0.70308–0.70384), suggests that magma diversity was well preserved within these crystal mushes. Moreover, significant magma mixing from variable sources occurred at mid-crustal levels. These findings illustrate the presence of polybaric, heterogeneous mush zones, with slow crystallization occurring at various depths beneath the SWIR. This study highlights the intricate interplay among multiple magma sources, replenishment events, and crystallization environments, providing new insights into the formation and variability of the oceanic crust at ultraslow-spreading ridges.